An Analysis of Illocutionary Acts in â€œA Thousand Splendid Sunsâ€ Novel - Adinda, Ismi (CV. Pena Persada, 2018)
The goal of this research is to understand how the listener translates the speaker‘s idea and to know what the speaker‘s purpose or mean in ―A Thousand Splendid Suns‖ novel. To send the speaker‘s purpose, the speaker uses illocutionary act in order to the listener performs or does something as the speaker‘s wants. The research method used in this study is descriptive-qualitative. The types of illocutionary acts are described and the result of study uses J.R. Searle theory. From some kinds of illocutionary acts are formed such as: Representatives, Directives, Commisives, Expressive, and Declarations. Then, from the types of Illocutionary Act can be used to classify what the speaker is saying, such as asserting, concluding, requesting, promising, threatening, offering, apologizing, welcoming, congratulating, excommunicating, and marrying.